2017
DOI: 10.1371/journal.pone.0179469
|View full text |Cite
|
Sign up to set email alerts
|

5-Aza-2’-deoxycytidine in the medial prefrontal cortex regulates alcohol-related behavior and Ntf3-TrkC expression in rats

Abstract: Recent studies have indicated that DNA methylation plays an important role in the development of alcohol abuse. 5-Aza-2’-deoxycytidine (5-Aza-dc), an inhibitor of DNA methyltransferases, was FDA approved for myelodysplastic syndrome treatment. However, it is unclear whether 5-Aza-dc is involved in alcohol abuse. In this study, using a chronic alcohol exposure model in rats, 5-Aza-dc was injected into the medial prefrontal cortex (mPFC). Alcohol-drinking behavior and the anxiety related behavior were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…DNAm in the brain plays an important role in learning and memory (Zovkic et al 2013), and evidence is accumulating that DNAm is also important in AUD (Tulisiak et al 2017). Increased expression of DNMT1 protein, and DNMT3a and 3b genes in rodent brains, and decreased expression of DNMT3A and 3B genes in human blood samples have been observed after chronic ethanol exposure (Barbier et al 2015; Bonsch et al 2006; Warnault et al 2013; Qiao et al 2017). The difference in DNMT3A and 3B expression between brain and blood samples may be due to species differences (rat vs. human), different tissue-specific responses to ethanol, or duration or timing of alcohol exposure.…”
Section: Epigenetic Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…DNAm in the brain plays an important role in learning and memory (Zovkic et al 2013), and evidence is accumulating that DNAm is also important in AUD (Tulisiak et al 2017). Increased expression of DNMT1 protein, and DNMT3a and 3b genes in rodent brains, and decreased expression of DNMT3A and 3B genes in human blood samples have been observed after chronic ethanol exposure (Barbier et al 2015; Bonsch et al 2006; Warnault et al 2013; Qiao et al 2017). The difference in DNMT3A and 3B expression between brain and blood samples may be due to species differences (rat vs. human), different tissue-specific responses to ethanol, or duration or timing of alcohol exposure.…”
Section: Epigenetic Modifiersmentioning
confidence: 99%
“…In alcohol-dependent rats, infusion of RG108 into the cerebral ventricles resulted in decreased alcohol intake after a three-week period of forced abstinence when compared with vehicle-treated rats (Barbier et al 2015). Similarly, infusion of decitabine into the medial prefrontal cortex of chronically drinking rats decreased ethanol intake but increased anxiety-like behavior (Qiao et al 2017). The timing of administration appears to be important for the ability of DNMT inhibitors to reduce ethanol drinking.…”
Section: Epigenetic Modifiersmentioning
confidence: 99%
“…Studies on anxiety, one of the typical affective consequences observed after adolescent CIE exposure, has primarily focused on the amygdala [29], bed nucleus of the stria terminalis (BNST) [30], hippocampus [31], and prefrontal cortex (PFC) [32]. However, the potential link between adolescent CIE-induced anxiety-like behaviors and the striatum has been substantially supported by data from our lab and others as follows.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the observation group received CAG regimen combined with decitabine and achieved a total effective rate of 85.29%, which was higher than that of the control group (61.76%); this is attributable to decitabine, a demethylating drug with a distinct inhibitory effect on methyltransferase, which has an effect on some local highly demethylated CpG islands by inhibiting DNA methyltransferase to reactivate antioncogenes (Qiao et al 2017;Xie et al 2019). Moreover, its demethylation function does not obviously intervene with other genes that are hypomethylated and worsen the instability of genomes (Momparler et al 2017).…”
Section: Discussionmentioning
confidence: 55%